Helicobacter pylori‐negative gastric cancer: Characteristics and endoscopic findings. Issue 5 (16th April 2015) - Yamamoto, Yorimasa; Fujisaki, Junko; Omae, Masami; Hirasawa, Toshiaki; Igarashi, Masahiro
<x xml:space="preserve">Abstract</x> Helicobacter pylori (H. pylori) leads to chronic gastritis and eventually causes gastric cancer. The prevalence of H. pylori infection is gradually decreasing with improvement of living conditions and eradication therapy. However, some reports have described cases of H. pylori‐negative gastric cancers (HpNGC), and the prevalence was 0.42–5.4% of all gastric cancers. Diagnostic criteria of HpNGC vary among the different reports; thus, they have not yet been definitively established. We recommend negative findings in two or more methods that include endoscopic or pathological findings or serum pepsinogen test, and negative urease breath test or serum immunoglobulin G test and no eradication history the minimum criteria for diagnosis of HpNGC. The etiology of gastric cancers, excluding H. pylori infection, is known to be associated with several factors including lifestyle, viral infection, autoimmune disorder and germline mutations, but the main causal factor of HpNGC is still unclear. Regarding the characteristics of HpNGC, the undifferentiated type (UD‐type) is more frequent than the differentiated type (D‐type). The UD‐type is mainly signet ring‐cell carcinoma that presents as a discolored lesion in the lower or middle part of the stomach in relatively young patients. The gross type is flat or depressed. The D‐type is mainly gastric adenocarcinoma of the fundic gland type that presents as a submucosal tumor‐like or flat or depressed lesion in the middle and upper part of the stomach in relatively older patients. Early detection of HpNGC enables minimally invasive treatment which preserves the patient's quality of life. Endoscopists should fully understand the characteristics and endoscopic findings of HpNGC.